The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/adsc.201700726
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium‐Catalyzed Synthesis of Multiaryl‐substituted Naphthols via a Removable Directing Group

Abstract: Arene homologation employing internal alkynes as coupling partners and 2-pyridyloxyl as directing group through dual CÀH bond functionalization was accomplished using (pentamethylcyclopentadienyl)-rhodium(III) chloride dimer as a precatalyst. This protocol proved tolerant of synthetically valuable functional groups, and provided an expeditious access to highly congested naphthalene derivatives in moderate to good yields. Furthermore, the pyridyl moiety could be removed to furnish the versatile (OH)-free naphth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 92 publications
(5 reference statements)
0
11
0
Order By: Relevance
“…Unfortunately, the reaction with alkyl or heteroarylalkynes did not occur, and asymmetric alkynes resulted in very poor regioselectivity. 891 Acylation reactions were reported by Wu and Huo, using aldehydes and acyl chlorides as reactants. The first method ( Scheme 148C ) 892 uses TBHP as oxidant and follows the mechanism depicted in Scheme 118 , resulting mostly in monoacylation (difunctionalisation is substrate-dependent), giving low yields for strongly EWG-substituted phenols.…”
Section: Heterocyclic Dgs In C–h Functionalisationmentioning
confidence: 99%
“…Unfortunately, the reaction with alkyl or heteroarylalkynes did not occur, and asymmetric alkynes resulted in very poor regioselectivity. 891 Acylation reactions were reported by Wu and Huo, using aldehydes and acyl chlorides as reactants. The first method ( Scheme 148C ) 892 uses TBHP as oxidant and follows the mechanism depicted in Scheme 118 , resulting mostly in monoacylation (difunctionalisation is substrate-dependent), giving low yields for strongly EWG-substituted phenols.…”
Section: Heterocyclic Dgs In C–h Functionalisationmentioning
confidence: 99%
“…A further example highlighting the use of the popular rhodium(III) catalyst [(Cp*RhCl 2 ) 2 ] in naphthol synthesis was shown by Cui and co‐workers. [ 51 ] Their method involves a C–H bond functionalization of 2‐pyridyloxyls 38 (pyridine nitrogen directing the C(sp 2 )‐H insertion on the phenol ring), followed by subsequent insertion of internal alkynes 39 . Two key subsequent rhodacycle formations ensue, followed by a second alkyne 39 insertion and reductive elimination to yield polyarylated naphthalenes 40 in good yields.…”
Section: Synthesis Of Substituted Naphthols From Alkyne Materialsmentioning
confidence: 99%
“…Based on these observations and the literature precedents, possible catalytic cycles for both transformations are given in Scheme . First, cyclometalation of 1a generates a five-membered rhodacyclic intermediate A .…”
mentioning
confidence: 91%
“…Recently, Rh­(III)-catalyzed C–H bond annulation with alkynes has evolved into a powerful tool for the preparation of highly substituted polycyclic aromatic compounds. In particular, several novel fused polycyclic (hetero)­arenes could be readily synthesized by annulation reactions of (hetero)­arenes with alkynes under Rh­(III) catalysis via double C–H activation involving chelation-assisted ortho C–H activation and subsequent rollover or nonrollover C–H activation. , Notably, the reaction pathway between rollover and nonrollover annulation can be switched by varying the reaction conditions, thereby delivering different types of products from the same substrates. For example, Miura and Satoh et al found that Rh­(III)-catalyzed rollover annulation of 1-phenyl-1 H -pyrazoles with 1 equiv of alkynes could give 4,5-disubstituted pyrazolo­[1,5- a ]­quinolones (Scheme a, right), while the nonrollover annulation of 1-phenyl-1 H -pyrazoles with 2 equiv of alkynes afforded 1-(5,6,7,8-tetrasubstituted naphthalen-1-yl)-1 H -pyrazoles as the products under slightly modified conditions (Scheme a, left) .…”
mentioning
confidence: 99%